Evaluation of a fish meal analogue as a replacement for fish meal in practical diets for Pacific white shrimp Litopenaeus vannamei. (13th October 2017) - Qiu, X.; Tian, H.; Davis, D.A.
Abstract: Three six‐week growth trials and a digestibility trial were conducted to evaluate a fish meal analogue (FMA) as a replacement for fish meal (FM) in shrimp feeds. Trials 1 and 2 evaluated and confirmed the potential of FMA supplementation (0, 48.5, 97, 145.5 and 194 g/kg) as a replacement for FM up to 200 g/kg without balancing for phosphorus (P) in practical diets for juvenile Pacific white shrimp L. vannamei . At the end of trial 1, shrimp offered diets containing 48.5 g/kg FMA exhibited significantly higher weight gain (WG) than those fed with the diet containing 145.5 g/kg FMA. At the end of trial 2, dietary FMA inclusion at 48.5 and 97 g/kg significantly improved WG and protein retention (PR), while reducing FCR and protein content of shrimp body compared to the diet containing 194 g/kg FMA. To determine whether P deficiency is the cause of reduced growth, the third trial was conducted utilizing equivalent diet but balanced for P. At the end of trial 3, shrimp fed diet containing 48.5 g/kg FMA+P showed significantly higher WG and PR than those fed diet containing 145.5 g/kg FMA+P. No decreasing trend of growth was detected in the diets containing FMA compared to the FM‐based diet. Apparent digestibility coefficients of dry matter, energy, protein and amino acids of FMA were determined using chromic oxide as an inert maker and the 70:30 replacement technique. The energy, protein and individual amino acid digestibility of FMA were significantly lower than those of soybean meal and FM which were run at the same time. Results of this work indicate that FMA can replace up to 200 g/kg FM in shrimp diets with supplemental inorganic P. Given the good growth across the range of inclusion without any indication of a growth depression, the low nutrient digestibility of FMA may be due to an atypical response or the product simply does not work with the testing technique.